Eco-friendly additive construction: Analysis of the printability of earthen-based matrices stabilized with potato starch gel and sisal fibers - Silva, G.; Ñañez, R.; Zavaleta, D.; Burgos, V.; Kim, S.; Ruiz, G.; Pando, M.A.; Aguilar, R.; Nakamatsu, J. (Elsevier, 2022)
3D printing for construction purposes is a disruptive technology with the potential for rapid and massive applications making it a feasible alternative for social housing, temporary shelters after disasters, and, recently, for extraterrestrial habitats. However, most of the matrices used for construction by 3D printing are based on hydraulic cement as the main constituent, which is not easily available in remote locations and is an important greenhouse gases generator. Therefore, a good understanding to formulate and evaluate alternative matrices using soil and organic materials with the required fresh and hardened-state properties compatible with this emerging technology is needed. This article studies the printable capabilities of eco-friendly earthen-based matrices which uses potato starch as a natural stabilizer for raw soil mortars aiming to obtain 3D printed filaments with adequate fresh and hardened-states properties. The aqueous starch gel was combined with sisal fibers in the printing mixture to control shrinkage cracking problems during hardening. The optimization of the dosage of the stabilizer was carried out considering different tests in fresh and hardened printed filaments namely, pumpability and extrudability, stacking, shear vane, shrinkage cracking, Vicat needle, compression strength, and capillarity absorption tests. The results indicate that printable earthen-based matrices reinforced with 1 % of sisal fibers by weight of soil and stabilized with aqueous starch gels with concentrations up to 5 % (w/w) showed improved workability and minor cracking and can be used for 3D printing. These promising results in the field of material science combined with novel 3D printing technology that is also presented in the article open new lines of research for eco-friendly alternatives for the construction industry.
Keywords: 3D printing in Construction; Additive Manufacturing; https://purl.org/pe-repo/ocde/ford#2.01.01